Gaga feminism sex, gender, and the end of normal - Halberstam, J. Jack 1961- (Queer action/queer ideas, 2012)
Analyzes the transformative political and societal shifts of recent decades that have paved the way for revolutionary conceptualizations of gender and marriage, using Lady Gaga as a symbol of a new era that embraces sexual fluidity.